ANALISIS QUESTIONING SKILL GURU BERBASIS HOTS PADA PEMBELAJARAN PKN DI MADRASAH IBTIDAIYAH - Citra Nur Pratiwi; Abdul Gani Jamora Nasution (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
This paper has an important purpose to be expressed focusing on three targets. First, to find out the teacher's skills in formulating HOTS-based questioning skills (QS). Second, to see the learning output using HOTS-based (QS). Third, to find out the obstacles faced by teachers in HOTS-based (QS). The three formulations are seen PKn learning at MIS Madinatussalam. In order to get maximum results, the researcher used a descriptive qualitative research method with data collection techniques, namely observation, interviews, and documentation. Then, the validity of the data was tested through triangulation. The results of the study showed that first, in formulating HOTS-based (QS), Civics teachers have five steps. Starting from understanding the learning objectives, based on Bloom's taxonomy, the context of students' lives, utilizing group discussions, and constructive feedback. Second, the output of QS learning can be found five advantages, namely critical and analytical thinking skills, the ability to argue and express opinions appropriately, the ability to evaluate problems, the ability to be creative in solving citizenship problems, and improving character towards citizenship. Third, the obstacles faced by teachers in implementing HOTS-based QS are limited time, limited teacher mastery, diverse student characteristics, limited resources and facilities, and challenges in creating a discussion atmosphere. The findings of this study have significance in the skills of a teacher in learning, who must master the complexity of competencies in learning. especially in making a question. The target is to achieve learning objectives according to the demands of KKM and of course accommodate the complexity of student potential